Penguatan Kesiapan IKM Informatika Melalui Pelatihan Jaringan MAN dan SMK di Lombok Timur: Strengthening Readiness for Informatics IKM through Network Training at MAN and Vocational Schools in East Lombok - Baiq Desi Dwi Arianti; Jamaluddin Jamaluddin; Kholida Ismatulloh; Yosi Nur Kholisho; Rasyid Hardi Wirasasmita; Hartini Haritani; Marfuatun Marfuatun (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2024)
The advancement of science and technology in the era of the Industrial Revolution 4.0 and Society 5.0 has impacted various aspects of life, including education. In response, the Indonesian government, through the Ministry of Education and Culture Regulation Number 36 and 37 of 2018, reintegrated informatics subjects into the Merdeka Belajar curriculum. However, the readiness of schools to implement this curriculum remains a challenge, particularly due to the lack of competent teachers in informatics and limited facilities. This Community Service activity aims to enhance students' understanding and skills in basic computer networks through training and mentoring at MAN 1 Selong and SMK-Qurrota’ayun. The training involved lecturers and students from the Informatics Education Study Program and was conducted over three intensive sessions. The methods used included theoretical material delivery, practical simulations, and small group mentoring to ensure that each participant could understand and apply the given material. Pretest results indicated that the majority of participants had a low understanding of computer networks. However, after the training, there was a significant improvement in participants' understanding and skills, as shown by the posttest results. The "very-understanding" level increased from 0% to 5%, "understanding" from 2% to 40%, while "less understanding" decreased from 11% to 45%, and "not understanding at all" from 87% to 10%. The conclusion from this activity is that hands-on training methods and intensive mentoring effectively enhance students' technical competencies in computer networks. This training model can serve as a reference for other skill development programs in the field of education